2015
DOI: 10.1007/s10549-015-3410-7
|View full text |Cite
|
Sign up to set email alerts
|

VEGF-A levels in bevacizumab-treated breast cancer patients: a systematic review and meta-analysis

Abstract: Bevacizumab may improve outcomes of patients with breast cancer, but the absence of an established biomarker hampers patient selection and researchers´ ability to demonstrate a clear survival benefit. Its putative target, circulating VEGF-A, emerged as the main candidate and we sought to identify the relationship between VEGF-A levels and outcomes through systematic review. We searched electronic databases and meeting proceedings for randomized controlled trials (RCTs) comparing the addition of bevacizumab to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
16
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 37 publications
(17 citation statements)
references
References 32 publications
1
16
0
Order By: Relevance
“…It is interesting to note that the measured secreted levels of VEGF were relatively low compared to some of the other proteins detected. However, comparable, picogram levels of VEGF-A have been reported in the plasma of cancer patients [ 25 ] and to have significant effects on endothelial function [ 26 ]. The pathogenic role of VEGF in tumour growth is well documented (reviewed in [ 17 ]) and not only has enhanced VEGF expression been observed in all forms of NSCLC, but also high serum levels have been correlated with poor prognosis in patients [ 27 , 28 ].…”
Section: Discussionmentioning
confidence: 86%
“…It is interesting to note that the measured secreted levels of VEGF were relatively low compared to some of the other proteins detected. However, comparable, picogram levels of VEGF-A have been reported in the plasma of cancer patients [ 25 ] and to have significant effects on endothelial function [ 26 ]. The pathogenic role of VEGF in tumour growth is well documented (reviewed in [ 17 ]) and not only has enhanced VEGF expression been observed in all forms of NSCLC, but also high serum levels have been correlated with poor prognosis in patients [ 27 , 28 ].…”
Section: Discussionmentioning
confidence: 86%
“…Stepwise investigation demonstrated miR-29c directly bound to the 3′-UTR region of VEGFA, and reduced VEGFA protein expression in breast carcinoma cells, coupled with the downregulation of HIF-α. To deeply understand the molecular mechanisms of miR-16-5p in vivo , we found that miR-16-5p overexpression evidently downregulated HIF-α and VEGF protein expression in nude mice tumor tissues, which were an accepted fact that these two proteins play an essential role in the development and progression of many tumors by multiple different mechanisms [ 36 – 46 ]. These findings highlight the potential therapeutic value of miR-16-5p in breast carcinoma, and combination of miR-16-5p with the related signaling pathway of HIF-α and VEGFA may be an effective molecular target for the patients with breast carcinoma in future.…”
Section: Discussionmentioning
confidence: 99%
“…Despite comprehensive research, the mechanism of bevacizumab resistance remains poorly understood. One possible reason is the difficulty of identifying molecular biomarkers associated with the synergistic effect of bevacizumab and cytotoxic chemotherapy in humans (20,21). We believe that intrinsic resistance to bevacizumab is more dependent on physiologic changes during treatment than genomic alterations (22,23).…”
Section: Introductionmentioning
confidence: 99%